How effective is regional spatial plan for coastal habitat quality? An exercise in Bengkulu City, Indonesia - Della Ayu Lestari; Yonvitner; Ario Damar; Fery Kurniawan; I Wayan Nurjaya (Journal of Coastal Conservation, 2026)

Carbon stocks on the intertidal seagrass meadow of the Indonesian Islands: Spatial and anthropogenic activities variability - Fery Kurniawan; Agustin Rustam; Robba Fahrisy Darus; Fauziyah; Almira Nadia Kusuma; Muhammad Noval Alghifari; Luky Adrianto; Yonvitner (Continental Shelf Research, 2026)

The impact of the Covid‐19 pandemic on export of lacustrine African cichlids and ornamental fishkeeping in the Czech Republic - Jiří Patoka; Yonvitner; Ernik Yuliana; Jindřich Novák; Barbora Patoková; Oldřich Kopecký; Filip Tomíček; Michael F. Tlusty (Biologia, 2025)
Ornamental aquaculture is an economically important sector with millions of enthusiasts over the planet. Many countries produce and export animals designated for the aquarium trade. According to the historical aspects, the Czech Republic remains one of the major producers of freshwater aquarium animals. Here we evaluate the trade impact of the COVID-19 pandemic on the dynamic of the export of captive-bred lacustrine African cichlids from the Czech Republic. Via questionnaire survey, we also addressed how the numbers of ornamental fishkeepers changed. The export volume of individual fish increased by 50% between 2018 and 2019 with most fish delivered to Thailand, South Korea and Hong Kong. Exports declined between 2019 and 2023 and number of individuals were back to 2018 levels while 33% fewer species were shipped in 2023 compared to 2018. The popularity of ornamental fishkeeping remains high with 1:11 (9%) people owning at least one indoor aquarium at home. Thus, a negative impact of the pandemic was not observed in the Czech Republic and the trade seems steady. Also, the popularity of ornamental fishkeeping remains high and has not been negatively impacted by the pandemic. Further monitoring of the aquarium trade and livestock is necessary to track how the trade may change as other global stressors occur.

The Jekyll and Hyde fish: Phenotype as a determinant of the invasion potential of Polypterus senegalus Cuvier, 1829 - Tereza Valchářová; Pavel Horký; Surya Gentha Akmal; Yonvitner; Jiří Patoka; Ondřej Slavík (Applied Animal Behaviour Science, 2025)

Vulnerability Status of the Coral Ecosystem in Kepulauan Seribu Marine National Park, Indonesia - Yonvitner; Syamsul Bahri Agus; Dea Fauzia Lestari; Riza Pasaribu; Eko Supriyanto; Cahyo Widodo; Ayub Sugara; Jiří Patoka; Surya Gentha Akmal (Coastal Management, 2022)

Vulnerability of marine resources to small‐scale fishing in a tropical area: The example of Sunda Strait in Indonesia - Yonvitner Yonvitner; Josep LIoret; Mennofatria Boer; Rahmat Kurnia; Surya Gentha Akmal; Ernik Yuliana; Diarsi Eka Yani; Sílvia Gómez; Ludivica Endang Setijorini (Fisheries Management and Ecology, 2020)
Although small‐scale fisheries (SSF) play an important socio‐economic role in developing nations, overfishing seems to be increasing the risk of stock vulnerability. This study aims to quantify the pressure of SSF on fish stocks in Sunda Strait (Indonesia) using several biological indicators that are important in quantifying fishing pressure. Data on these indicators were collected monthly for three years (2012–2014) in one of the main fishing ports of the area. The results provide evidence that, although SSF would appear to be the most environmentally sustainable of all the fishing techniques being used today in the coastal waters of Indonesia, the impact of SSF fishing on juvenile fishes in certain areas such as the Sunda Strait must not be underestimated. The results also show the need to protect immature fish of species that are not only commercialised but are also important in subsistence fisheries. Although further studies are needed to assess the impact of SSF on fish stocks in the area, it is suggested management recommendations that include the implementation of marine‐protected areas in nursery grounds and establishing minimum landing sizes well above the size‐at‐maturity for each species, are needed.

Phytoplankton Biomass Dynamics in Tropical Coastal Waters of Jakarta Bay, Indonesia in the Period between 2001 and 2019 - Ario Damar; Franciscus Colijn; Karl-Juergen Hesse; Luky Adrianto; Yonvitner; Achmad Fahrudin; Fery Kurniawan; Ageng Dwi Prismayanti; Siti Mira Rahayu; Bambang Yudho Rudianto; Agus Ramli (Journal of Marine Science and Engineering, 2020)
A study of nutrients, underwater light dynamics, and their correlation with phytoplankton biomass was conducted in the tropical estuary of Jakarta Bay, Indonesia, in the dry season during the period from 2001 to 2019. This study analyzed the spatial and temporal dynamics of phytoplankton biomass and its correlation with phytoplankton biomass. There was significant increase in nutrient concentration in Jakarta Bay, with annual means of 27.97 µM dissolved inorganic nitrogen (DIN) and 11.31 µM phosphates in 2001, increasing to 88.99 µM DIN and 25.92 µM phosphates in 2019. Increased mean nutrient concentrations were accompanied by increased mean phytoplankton biomass, from 15.81 µg Chl-a L−1 in 2001 to 21.31 µg Chl-a L−1 in 2019. The eutrophication status of Jakarta Bay waters was calculated using the Tropical Index for Marine Systems eutrophication index, which showed increased areas of hyper-eutrophic and eutrophic zones, while the mesotrophic area decreased. The hyper-eutrophic zone dominated the areas around river mouths and the inner part of the bay, while eutrophic status was observed in the middle part of the bay and mesotrophic status was found in the outer part of the bay. The area of hyper-eutrophic water increased 1.5-fold, from 75.1 km2 in 2001 to 114.0 km2 in 2019. Increasing eutrophication of the bay has had negative ecological consequences including algal blooms, hypoxic conditions, and mass mortality of marine biota, and it urgently requires remediation.